ALIRAN KALAM SALAFIYAH - Muhammaddin Muhammaddin (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
Mu’tazila had reached the power in Abbasiya Dinasty. Mu’tazilah main controversial thought was the notion that Al Quran is a creature. All peoples and scholars were forced to follow the thought. Meanwhile there was a scholar who strongly opposed the notion. He was Imam Ahmad Ibn Hambal. He was often threated, tortured and busted by the ruler. Imam Ahmad Ibn Hambal thought was inspired by the new theological school, Salaf School. Salaf was the theological school following the Imam Ahamad Ibn Hambal thought which was formulated by Imam Ahmad Ibn Taimiyah. As the Asyariyah school, Salaf was the reaction against the Mu’tazilah thought. The paper will discuss the two main scholar of Salafi School namely Imam ibn Hambal and Ibn Taimiyah. It includes their biographies, toughts, and their interpretation on Mutasyabihat, the verses which have no clear on meaning and the Allah’s attributes.